2021
DOI: 10.1002/mrm.29022
|View full text |Cite
|
Sign up to set email alerts
|

A 31‐channel integrated “AC/DC” B0 shim and radiofrequency receive array coil for improved 7T MRI

Abstract: Purpose To test an integrated “AC/DC” array approach at 7T, where B0 inhomogeneity poses an obstacle for functional imaging, diffusion‐weighted MRI, MR spectroscopy, and other applications. Methods A close‐fitting 7T 31‐channel (31‐ch) brain array was constructed and tested using combined Rx and ΔB0 shim channels driven by a set of rapidly switchable current amplifiers. The coil was compared to a shape‐matched 31‐ch reference receive‐only array for RF safety, signal‐to‐noise ratio (SNR), and inter‐element nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Also, slice-by-slice (slab-selective compared to the volume shim) shimming approaches have greatly improved the utility of parallel transmission with improved homogenous B 1 field across the slabs in the heart while decreasing the SAR level [65,66]. These studies aim to eventually include dynamic shim updating on the selected volume in the heart, as has been experimented with within the brain studies at ultra-high-field ≥7 Tesla [67,68]. Overall considerations on the heart shimming include: (i) using slab-selective approaches shimming to minimize the field distribution variations (shimming standard deviation (SD)), (ii) optimizing high-order shims, (iii) temporal B 0 -field variations with regards to cardiac cycle and respirationinduced, (iv) shimming of oblique orientations, (v) develop dynamic shimming interface by rapid field mapping using slab-specific or cardiac phase-specific mapping sets, and (vi) the emerging use of artificial intelligence in compensating the field variations [45,63,66,[69][70][71].…”
Section: Coil and Dynamic Shimming Approachesmentioning
confidence: 99%
“…Also, slice-by-slice (slab-selective compared to the volume shim) shimming approaches have greatly improved the utility of parallel transmission with improved homogenous B 1 field across the slabs in the heart while decreasing the SAR level [65,66]. These studies aim to eventually include dynamic shim updating on the selected volume in the heart, as has been experimented with within the brain studies at ultra-high-field ≥7 Tesla [67,68]. Overall considerations on the heart shimming include: (i) using slab-selective approaches shimming to minimize the field distribution variations (shimming standard deviation (SD)), (ii) optimizing high-order shims, (iii) temporal B 0 -field variations with regards to cardiac cycle and respirationinduced, (iv) shimming of oblique orientations, (v) develop dynamic shimming interface by rapid field mapping using slab-specific or cardiac phase-specific mapping sets, and (vi) the emerging use of artificial intelligence in compensating the field variations [45,63,66,[69][70][71].…”
Section: Coil and Dynamic Shimming Approachesmentioning
confidence: 99%
“…While previous work has shown that FIDnavs can retrospectively compensate for higher-order spatiotemporal field changes, the second-order shim coils on the scanner are not designed for rapid switching. Higher-order field stabilization requires use of custom shim array coils 42,43 and will be investigated in future work.…”
Section: Extensions and Future Workmentioning
confidence: 99%
“…Toroids have been previously used as inline chokes; in spatially distributed, rigid, inductively coupled traps; and as transceive coils in interventional devices. 9,[17][18][19] We propose to use them as subcomponents in our distributed design because they are mostly self-shielded, especially with a large number of turns. Caterpillar traps are illustrated and compared to conventional traps in Figure 1A.…”
Section: Introductionmentioning
confidence: 99%